PENGARUH MOTIVASI KERJA TERHADAP KUALITAS PELAYANAN PUBLIK PADA KANTOR KELURAHAN SUNGAI PINANG LUAR KECAMATAN SAMARINDA KOTA - ., Heni (PREDIKSI, 2012)
ABSTRACTThe purpose of this study was to determine if the work environment has an impact on employees working spirit. Therefore to get this writer doing research in the Office of Public Works in East Kalimantan Province.This type of research are verified by the author, which is a study that you want to know and find the relationship between the two variables is to analyze the results of the study using a random lottery technique 50% of the 48 people to 24 employees.To prove the existence of the effect between the two variables the authors use Moment Correlation formula. Based on data analysis and hypothesis testing, it is known that the relationship between the work environment and employee morale Settlements In Field Office Department of Public Works in East Kalimantan Province was very good.